2013
DOI: 10.1016/j.jalz.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of memory endophenotypes for association with CLU, CR1, and PICALM variants in black and white subjects

Abstract: Background Genetic variants at the CLU, CR1 and PICALM loci associate with risk for late-onset Alzheimer’s disease (LOAD) in genome-wide association studies (GWAS). In this study, our aim was to determine whether the LOAD risk variants at these three loci influence memory endophenotypes in African-American and Caucasian subjects. Methods We pursued an association study between single nucleotide polymorphism (SNP) genotypes at the CLU, CR1 and PICALM loci and memory endophenotypes. We assessed African-America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
5
24
1
1
Order By: Relevance
“…In the current study, we evaluated the association of nine LOAD risk GWAS loci SNPs for association with memory scores in a longitudinally assessed cohort and identified strong association between APOE ε4 with both baseline logical memory and increased rate of memory decline, as expected(10-13). As in our prior study(27), we also identified lower memory scores at baseline associated with the risk allele of the CLU locus SNP rs11136000. Although this consistency may be expected given that the cohort from our prior study and the current one largely overlap, the approach used in this study is distinct because we evaluated baseline and longitudinal cognitive change instead of the last memory score as in our prior work.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, we evaluated the association of nine LOAD risk GWAS loci SNPs for association with memory scores in a longitudinally assessed cohort and identified strong association between APOE ε4 with both baseline logical memory and increased rate of memory decline, as expected(10-13). As in our prior study(27), we also identified lower memory scores at baseline associated with the risk allele of the CLU locus SNP rs11136000. Although this consistency may be expected given that the cohort from our prior study and the current one largely overlap, the approach used in this study is distinct because we evaluated baseline and longitudinal cognitive change instead of the last memory score as in our prior work.…”
Section: Discussionsupporting
confidence: 81%
“…Genetic variants that associate with cognition in a non-time-dependent fashion may suggest static effects, whereas those that associate with rate of cognitive decline may imply a dynamic influence on biological mechanisms underlying cognitive outcomes. We previously evaluated three LOAD risk GWAS SNPs at CLU , CR1 and PICALM loci for association with verbal and non-verbal episodic memory scores at last evaluation and identified better memory scores in Caucasian subjects with the protective CLU rs11136000 SNP alleles and worse scores in African-American subjects with the risky CR1 SNP (rs6656401, rs3818361) alleles(27). In the current study, we evaluated the association of nine LOAD risk GWAS loci SNPs for association with memory scores in a longitudinally assessed cohort and identified strong association between APOE ε4 with both baseline logical memory and increased rate of memory decline, as expected(10-13).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results conform to a model of AD pathology where early susceptibility and/or vulnerability is associated with initial increases in brain activation during complex tasks, followed by reduced activation once compensatory mechanisms have failed and the disease manifests clinically [14]. The C risk genotype on CLU rs11136000 may potentially modulate plasma clusterin [49,50] and reduce the efficiency of Ab 1-42 sequestration [51] and is associated with diminished memory performance in later life [52,53], suggesting that CLU may be implicated in hallmark features of AD pathogenesis such as Ab 1-42 plaque aggregation [54,55]. Future work should consider how AD risk variants such as CLU rs11136000 may affect neural activity during healthy and pathological aging processes, and how this variation may be mediated by Ab .…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, previous studies did not report any positive associations for BIN1, whereas we found an association between BIN1 and general cognition (MMSE). These discrepancies could be explained by differences in design (for example, use of case/control design as in the study by Pedraza et al 35 ), choice of model for cognitive decline (for example, Sweet et al use a Bayesian analysis to model cognitive Table 4. Associations between LOAD-associated SNPs and cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%